A Cascade of Catastrophes Following Total Knee Arthroplasty: A Case Report and Literature Review on Sequential Periprosthetic Joint Infection and Iatrogenic Geniculate Artery Pseudoaneurysm - Agung Wahyudi; Yenti Sukarida (The International Journal of Medical Science and Health Research, 2025)
Introduction: Total Knee Replacement (TKR) is a highly successful, gold-standard procedure for end-stage osteoarthritis (OA), a condition with a rising global prevalence (Li et al., 2024). However, complications, while statistically rare, can be catastrophic. Periprosthetic Joint Infection (PJI), a leading cause of TKR failure (Ma et al., 2024), and iatrogenic vascular injuries represent two such devastating complications. This report details the unique and highly complex case of a patient who experienced both of these severe complications sequentially. It aims to elucidate the diagnostic challenges posed by this rare cascade of events, particularly the 'diagnostic masking' that occurs when a new, non-infectious complication mimics a septic recurrence. Case Illustration: We present the case of a 68-year-old male with a history of sub-optimally controlled Type-2 Diabetes Mellitus who underwent a primary TKR for severe osteoarthritis. Eight months postoperatively, he developed a chronic PJI with a draining sinus tract, definitively confirmed by the 2018 Musculoskeletal Infection Society (MSIS) criteria (Parvizi et al., 2018). The pathogen was identified as Methicillin-Sensitive Staphylococcus aureus (MSSA). This was successfully managed via the gold-standard two-stage revision, which included radical debridement, complete component explantation, insertion of a high-dose articulating antibiotic spacer (Welsh and Baumann, 2021), a 6-week course of intravenous antibiotics, and subsequent definitive reimplantation. Ten days following the final reimplantation, the patient presented to the Emergency Department with an acute, massive, and excruciatingly painful sterile hemarthrosis. Crucially, his systemic inflammatory markers were normal. A high-stakes diagnostic workup, including Duplex Ultrasound and CT Angiography, revealed a pseudoaneurysm of the superior lateral geniculate artery (SLGA). This vascular injury was successfully treated with minimally invasive endovascular coil embolization (Melian et al., 2023), leading to complete resolution of symptoms and definitive salvage of the revision prosthesis. Discussion: This case highlights the critical diagnostic challenge of a recurrently swollen knee, especially when a patient's recent history of PJI creates a strong 'anchoring bias' toward recurrent infection. We provide a comprehensive review of the distinct diagnostic and management pathways for both chronic PJI—including the utility of the 2018 MSIS criteria (Parvizi et al., 2018) and the gold-standard two-stage revision—and the rare but limb-threatening geniculate artery pseudoaneurysm. For the latter, endovascular embolization (Melian et al., 2023; Puijk et al., 2022) represents the modern treatment of choice, particularly in a surgically hostile, multi-operated field (Luyckx et al., 2019). Conclusion: This report underscores the necessity of maintaining a broad differential diagnosis for a painful, swollen TKR, even in the face of a convincing infectious history. In a patient presenting with acute, large-volume, sterile hemarthrosis—a presentation distinct from their prior septic picture—a vascular etiology must be aggressively pursued. Normal inflammatory markers and a purely bloody aspirate are the key laboratory pivots that should immediately override a suspected infection diagnosis and prompt an emergent vascular imaging workup.